Analisis Trend Rasio Likuiditas Bank Muamalat Menggunakan Metode Least Square - Lubis, M. Zaky Mubarak; Rahmat, Ihsan; Agusti, Netta; Wiratha, Andre (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to see the development of Bank Muamalat's liquidity ratio in 2015-2018. This type of research is descriptive with a quantitative approach. The method used is Trend Analysis with least square method. The data collection technique used in this study is documentation. In this study, researchers used secondary data in the form of annual report Muamalat Bank in 2015-2018. The results showed that the development of Muamalat Bank liquidity for the 2015-2018 period in terms of FDR was 90 %, 95 %, 85 % dan 74 %. The comparison of the real value of FDR and the value of FDR Trends from 2015-2018 is 90%, 95%, 85% and 74% compared to 83.1%, 80.2%, 77.3% and 74.3%. This shows the tendency of trend values that are getting closer to the real value in 2018. Prediction of the value of FDR in 2019-2021 based on the equation Y = 86-2.9 (X) is 71.5%, 68.6% and 65.4%. The trend value shows a decrease in percentage which shows the stronger liquidity of Bank Muamalat in the same time as the composite index